2023
DOI: 10.3390/insects14020145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methyl Jasmonate Fumigation on the Growth and Detoxification Ability of Spodoptera litura to Xanthotoxin

Abstract: Methyl jasmonate (MeJA) is a volatile substance derived from jasmonic acid (JA), and it responds to interbiotic and abiotic stresses by participating in interplant communication. Despite its function in interplant communication, the specific role of MeJA in insect defense responses is poorly understood. In this study, we found that carboxylesterase (CarE) activities, glutathione-S-transferase (GSTs) activities, and cytochrome mono-oxygenases (P450s) content increased more after the feeding of diets containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…For example, Tianzi et al (2018) reported that the activities of GSTs and CarE were subsequently stimulated after C. anachoreta larvae that fed on MeJA-treated leaves. An increase in P450 activity in Helicoverpa armigera larvae that fed on MeJA-treated cotton leaves (Fan et al 2014);Chen et al (2023) demonstrated that MeJA effectively induced Spodoptera litura defense response, and lower and medium concentrations of MeJA induced higher activities of detoxification enzymes than higher concentrations. However, Yang et al (2022) reported a significant decrease in the immunity and detoxification metabolism of H. armigera after it fed on cotton treated with JA, indicating that exogenous phytohormone treatment could control pests by inhibiting insect detoxification metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tianzi et al (2018) reported that the activities of GSTs and CarE were subsequently stimulated after C. anachoreta larvae that fed on MeJA-treated leaves. An increase in P450 activity in Helicoverpa armigera larvae that fed on MeJA-treated cotton leaves (Fan et al 2014);Chen et al (2023) demonstrated that MeJA effectively induced Spodoptera litura defense response, and lower and medium concentrations of MeJA induced higher activities of detoxification enzymes than higher concentrations. However, Yang et al (2022) reported a significant decrease in the immunity and detoxification metabolism of H. armigera after it fed on cotton treated with JA, indicating that exogenous phytohormone treatment could control pests by inhibiting insect detoxification metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…2014); Chen et al . (2023) demonstrated that MeJA effectively induced Spodoptera litura defense response, and lower and medium concentrations of MeJA induced higher activities of detoxification enzymes than higher concentrations. However, Yang et al .…”
Section: Discussionmentioning
confidence: 99%